2012
DOI: 10.1016/j.marpol.2011.03.013
|View full text |Cite
|
Sign up to set email alerts
|

New metrics for managing and sustaining the ocean's bounty

Abstract: 2016-12-24T18:18:19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 2 publications
2
56
0
Order By: Relevance
“…Regarding the suitability of the different methods exposed, we agree with Tallis et al (2012) and Ringold et al (2013) who suggest that an open combination of the two scopes identified would provide the most information, firstly identifying the valuable ecosystem services to stakeholders, and secondly, ranking their preferences (i.e., the value). This is especially important in land management, where trade-offs between alternative land uses are frequent, and a selection of ecosystem services to be enhanced or decreased might be required (Hicks et al 2013).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Regarding the suitability of the different methods exposed, we agree with Tallis et al (2012) and Ringold et al (2013) who suggest that an open combination of the two scopes identified would provide the most information, firstly identifying the valuable ecosystem services to stakeholders, and secondly, ranking their preferences (i.e., the value). This is especially important in land management, where trade-offs between alternative land uses are frequent, and a selection of ecosystem services to be enhanced or decreased might be required (Hicks et al 2013).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, considering ecosystems from the perspective of each stakeholder or beneficiary (Ringold et al 2013) makes it easier to differentiate between the valuation of the service (what is supplied to the beneficiary) and the value given to it [what is weighted by the beneficiary (Tallis et al 2012)]. Furthermore, a previous understanding of the reasons why an ecosystem service is valued is essential for comparing valuation outcomes across studies (see examples of typologies of values in Hein et al 2006;Anthony et al 2009;and Chan et al 2012b).…”
Section: Stage 3: the Methods For Social Assessmentmentioning
confidence: 99%
“…Economists and social scientists have developed numerous approaches for evaluating the desirability of an environmental state to individuals or communities (Haab and McConnell 2002, Nelson 2006, Plummer 2009, Guerry et al 2012. Economists, for example, have methods for estimating values of ecosystem components that cannot readily be bought or sold (e.g., Carson et al 2001).…”
Section: Assess Ecosystem Preferencesmentioning
confidence: 99%
“…We first used radar plots (Fig. 2), which have proven useful for visualizing multidimensional trade-offs (e.g., Guerry et al 2012). However, because the numerical nature of radar plots may not resonate with some respondents (Bell 1984), we also developed stylized images (Fig.…”
Section: Reveal Desired Ecosystem Statementioning
confidence: 99%
“…Marine spatial planning efforts in Europe and, more recently, the U.S. are seeking to rationalize the use of coastal areas and lay the groundwork for comprehensive resource use plans (European Commission, 2011;Olsen et al, 2014). At the same time, coordinated research efforts are developing formal methods and tools to assess spatial tradeoffs in marine ecosystem services (Douvere, 2008;Hoagland et al, 2003;Kareiva et al, 2011;Tallis et al, 2011). All of this effort seeks to find ways to improve governance and inform the allocation of resources among diverse stakeholders for sustainable long term solutions that best use limited marine resources.…”
Section: Introductionmentioning
confidence: 99%